DNA barcodes reveal 63 overlooked species of Canadian beetles (Insecta, Coleoptera) - Pentinsaari, Mikko (Zookeys, 2019)
This study demonstrates the power of DNA barcoding to detect overlooked and newly arrived taxa. Sixty-three species of Coleoptera representing 25 families are studied based on DNA barcode data and morphological analysis of the barcoded specimens. Three of the species involve synonymies or previous taxonomic confusion in North America, while the first Canadian records are published for 60 species. Forty-two species are adventive in North America, and 40 of these adventive species originate from the Palaearctic region. Three genera are recorded from the Nearctic region for the first time: Coelostoma Brullé, 1835 (Hydrophilidae), Scydmoraphes Reitter, 1891 (Staphylinidae), and Lythraria Bedel, 1897 (Chrysomelidae). Two new synonymies are established: Mycetoporustriangulatus Campbell, 1991 (Staphylinidae) is a junior synonym of Mycetoporusreichei Pandellé, 1869, syn. nov. while Blediusphiladelphicus Fall, 1919 (Staphylinidae) is a junior synonym of Blediusgallicus (Gravenhorst, 1806), syn. nov. The previously suggested move of Cteniceratigrina (Fall, 1901) to the genus Pseudanostirus Dolin, 1964 (Elateridae) is formalized, resulting in Pseudanostirustigrinus (Fall, 1901), comb. nov.